2017
DOI: 10.1002/anie.201612138
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)‐Catalyzed Chemoselective Coupling of Cyclopropanols with Diazoesters: Ring‐Opening C−C Bond Formations

Abstract: Reported herein is an exceptional chemoselective ring-opening/C(sp )-C(sp ) bond formation in the copper(I)-catalyzed reaction of cyclopropanols with diazo esters. The conventional O-H insertion product is essentially suppressed by judicious choice of reaction conditions. DFT calculations provide insights into the reaction mechanism and the rationale for this unusual chemoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…470,471 In 2017, Wang and co-workers explored the reactivity of cyclopropyl alcohols with Cu carbenoids derived from diazo esters (Scheme 233). 472 undergo mechanochemical ring opening under pulsed ultrasonication (Scheme 234). 473 The authors found, through single-molecule force spectroscopy, that the methoxy substituent decreases the force required for rapid ring opening compared to analogous gem-dichlorocyclopropane derivatives.…”
Section: Pericyclic Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…470,471 In 2017, Wang and co-workers explored the reactivity of cyclopropyl alcohols with Cu carbenoids derived from diazo esters (Scheme 233). 472 undergo mechanochemical ring opening under pulsed ultrasonication (Scheme 234). 473 The authors found, through single-molecule force spectroscopy, that the methoxy substituent decreases the force required for rapid ring opening compared to analogous gem-dichlorocyclopropane derivatives.…”
Section: Pericyclic Reactionsmentioning
confidence: 99%
“…In 2017, Wang and co-workers explored the reactivity of cyclopropyl alcohols with Cu carbenoids derived from diazo esters (Scheme ). Reaction optimization revealed that the nature of the metal catalyst and reaction solvent were crucial to favor the formation of product 1062 resulting from cyclopropyl alcohol C–C bond cleavage, instead of the more traditional O–H insertion product. A range of 1-substituted cyclopropyl alcohols ( 1060 ) and diazo esters ( 1061 ) could be coupled in excellent yields.…”
Section: Othermentioning
confidence: 99%
“…Notable examples in this respect include allylation via copper catalysis of zinc homoenolates, 5 arylation via palladium homoenolates, 6 , 7 and amination via copper homoenolates, 8 among others. 9 Besides the homoenolate-based approach, recent years have also witnessed other mechanistically distinct types of ring-opening transformations of cyclopropanols, which employ coupling partners such as (fluoro)alkyl halides, 10 alkynylbenziodoxoles, 11 diazo compounds, 12 and so on 4 to access the corresponding β-functionalized ketones. Despite all the progress in the stoichiometric and catalytic cross-couplings via metal homoenolates, viable coupling partners have thus far been limited to polar organic electrophiles, and interception of a homoenolate with a nonpolar unsaturated hydrocarbon as a reaction partner has been elusive.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the reactions occurred smoothly, affording products in good yields. By‐products and a diminished yield were obtained for the synthesis of 5 s , cyclopropyl alcohols being prone to ring‐opening in presence of Cu I catalyst . The multiple unsaturations of substrate 5 w could explain why only partial conversion of the EBX reagent was observed, resulting in a moderate yield.…”
Section: Methodsmentioning
confidence: 99%